2023
DOI: 10.3390/su15043609
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Sustainable Fashion on Instagram

Abstract: Media discourse surrounding fashion and sustainability tends to be negative, emphasising the problems that exist across the various stages of the lifecycle of a garment. Although consumers are increasingly aware of at least some of the issues surrounding fashion and the environment, research suggests that the scale and complexity of the problem causes them to feel detached and uncertain about how to adapt their own behaviour in response. This research positions Instagram as a digital media platform through whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Carfora & Catellani (2022) [19] demonstrated that Instagram advertisements focused on sustainability can significantly enhance user engagement in sustainable practices, boosting consumer involvement, systematic processing, and purchase intentions. Similarly, Marcella-Hood (2023) [20] analyzed sustainable fashion content on Instagram, identifying a community of content creators who actively disseminate messages about sustainable fashion solutions, emphasizing the platform's role in building community awareness and education about sustainable practices.…”
Section: The Role Of Media In Shaping Sustainable Fashionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carfora & Catellani (2022) [19] demonstrated that Instagram advertisements focused on sustainability can significantly enhance user engagement in sustainable practices, boosting consumer involvement, systematic processing, and purchase intentions. Similarly, Marcella-Hood (2023) [20] analyzed sustainable fashion content on Instagram, identifying a community of content creators who actively disseminate messages about sustainable fashion solutions, emphasizing the platform's role in building community awareness and education about sustainable practices.…”
Section: The Role Of Media In Shaping Sustainable Fashionmentioning
confidence: 99%
“…Zhao et al (2022) [15] discuss how sustainable fashion brands strategically use social media to align their sustainability goals with their branding strategies, a crucial element in broadening their audience and influencing public perceptions [15]. Marcella-Hood (2023) [20] notes that building a community around sustainable fashion on platforms like Instagram involves more than sharing information; it requires fostering an environment where sustainable practices are normalized and valued.…”
Section: Towards Audience Perceptionmentioning
confidence: 99%
“…Así, aunque el engagement digital generado por el contenido visual de las marcas de moda en materia de sostenibilidad sí ha comenzado a ser parcialmente explorado (Milanesi et al, 2022;Marcella-Hood, 2023), ninguna de estas investigaciones se ha centrado en la naturaleza especifica de estas imágenes y en sus características. A su vez, debido a las limitaciones que conlleva el análisis cualitativo, las investigaciones previas se han limitado al estudio de un número reducido de marcas y de posts.…”
Section: Según El Informeunclassified
“…Kullanıcı sayısında en büyük artışı yaşayan sosyal ağlardan biri olarak konumlanan Instagram (Oltra vd., 2022(Oltra vd., , s. 1212, moda pazarında çok büyük bir etkiye sahip olup birçok işletme Instagram üzerinden pazarlama yapmakta ve birçok tüketiciyle iletişim kurmak için bir kanal olarak kullanılmaktadır (Na & Kim, 2019, s. 34). Bunun yanı sıra mevcut araştırma Instagram'ı, sürdürülebilir modanın üretildiği, tanıtıldığı ve moda içeriği aracılığıyla deneyimlendiği bir platform olarak konumlandırmaktadır (Marcella-Hood, 2023).…”
Section: Introductionunclassified